Success or Failure? Japan's National Strategy on Intellectual Property and Evaluation of Its Impact from the Comparative Law Perspective - Toshiko Takenaka (Washington University Global Studies Law Review, 2009)
This short Article will discuss Japan’s national IP strategy and changes brought to the IP system, focusing on features that follow the U.S. IP system. Additionally, it will review these changes from the comparative law perspective and evaluate whether the new system has accomplished its national strategy mission.
Keywords: Intellectual property -- Japan; Intellectual property -- United States; Comparative law; Intellectual property